STRUCTURAL EQUATION MODEL (SEM) FAKTOR YANG MEMENGARUHI KEPUASAN DAN LOYALITAS MAHASISWA - Riama Sibarani (FAKULTAS TEKNIK, 2021)
This researchs aims to examined and analyzed the direct effect of image, university, lecturer competence and service quality toward satisfaction and loyalty student. This study also examines and analyzes the indirect effect of the image of the college, lecturer competence, and service quality on student satisfaction and student loyalty as a mediating variable. The sample in this research were USNI students using simple randomsampling and purposive sampling methods. The sample criteria are students who have studied at least 4 (four) semesters. The variables analyzed are College Image, Lecturer Competence and Service Quality, satisfaction and loyalty. The methods and analysis tools are SEM and Path Analysis.